Community-based Awareness Model of Development Participation: A Case Study in Cisampih Village, Banjarsari District, Lebak Regency, Banten Province - Suhartono, Bambang; Rivai, Firman Hadi; Hia, Grace Aprilita; Darto, Mariman (KnE Social Sciences, 2025)
This research aims to understand how community awareness-based participation supports the implementation of development in Cisampih Village. It employs the qualitative descriptive method. The data used include primary and secondary data collected through in-depth interviews, focus group discussion (FGD) and documentation. The results of the research indicate that the community of Cisampih Village has participated in planning, implementation and evaluation of its development. The community is given the authority to provide corrections in the process development and if an error occurs in it, the community is allowed to report it directly to village officials and even to the village head.